Contributors to pedestrian distraction and risky behaviours during road crossings in Romania. Issue 6 (13th February 2017) - Hamann, Cara; Dulf, Diana; Baragan-Andrada, Erika; Price, Morgan; Peek-Asa, Corinne
Abstract : Objective: Pedestrian fatalities due to collisions with motor vehicles are a large public health problem in Romania, ranking them among the highest in Eastern Europe. The purpose of this study was to gain a better understanding of crash factors by examining how roadway and environmental characteristics contribute to pedestrian distraction and risky behaviours at pedestrian MVC (PMVC) locations in Cluj County, Romania. Methods: A sample of PMVC locations was selected from the 2010 Cluj County police reported crash database for on-site examination. A total of 100 sites were visited to collect details on site characteristics and typical pedestrian and driver behaviours. Variable distributions were examined and rate ratios of pedestrian distraction and risky behaviours were calculated. Results: Pedestrian distraction and risky behaviours were observed at rates of 6.3 and 24.3 per 100 observed pedestrians. The majority of distractions were related to electronic device use. Risky behaviours were evenly split between unpredictable, partial use of a crosswalk and midblock illegal crossings. Distractions and risky behaviours decreased as the number of pedestrians and average vehicle speeds at a site increased. RR of distraction was higher at intersections and locations with crosswalks. Conclusions: Pedestrian distraction was highly correlated with pedestrian risky behaviours at PMVC locations in Romania. Higher pedestrian volume was protective against pedestrian distraction and risky behaviours. Locations with painted crosswalks had increased distraction. Targeted distraction prevention, particularly at intersections and crosswalk locations, may contribute to the prevention of PMVCs.